Associations between the conicity index and kidney stone disease prevalence and mortality in American adults - Xianyu Dai; Yu Chang; Yuchuan Hou (Scientific Reports)
Abstract Kidney Stone Disease (KSD) is a prevalent urological condition, while abdominal obesity is on the rise globally. The conicity index, measuring body fat distribution, is crucial but under-researched in its relation to KSD and all-cause mortality. This study, using data from 59,842 participants in the NHANES (2007–2018), calculated the conicity index from waist circumference, height, and weight. Logistic regression and Cox models revealed a significant positive correlation: each 0.1 unit increase in the conicity index was linked to a 23% rise in KSD odds (OR: 1.23, 95% CI: 1.14, 1.35) and higher predictive ability compared to traditional measures (AUC = 0.619). In KSD patients, this increase corresponded to a 44% higher risk of all-cause mortality (HR: 1.44, 95% CI: 1.14, 1.82), and in non-KSD patients, a 53% increase (HR: 1.53, 95% CI: 1.37, 1.70). Serum albumin and Red Cell Distribution Width (RDW) partially mediated these relationships. Addressing central obesity could significantly lower the risks of KSD and mortality.